A method for testing the performance of metal amide hydrogen storage materials

Through the combination of thermogravimetric analysis and gas chromatography-mass spectrometer, the ammonia release amount of metal amino hydrogen storage materials was quickly determined, which solved the problem of long-term reversibility evaluation in the prior art, and achieved rapid screening and absorption Materials with good reversibility in hydrogen release and provide rich data and information to support further research on materials.

CN119001050BActive Publication Date: 2025-01-14CRINM (GUANGDONG) INST FOR ADVANCED MATERIALS & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411478112.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-14
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

In the prior art, it takes too long to evaluate the reversibility of metal amino hydrogen storage materials, and requires hundreds or thousands of cycle tests. It is difficult for traditional methods to directly determine the amount of ammonia gas, which affects the efficiency of material research and development.

Method used

Using a combination of thermogravimetric analysis and gas chromatography-mass spectrometer, the associated gas is collected through the thermogravimetric analyzer and transported to the gas chromatography-mass spectrometer for analysis, the first peak area of ​​the ammonia gas mass spectrometer is calculated, and the first peak area of ​​the ammonia gas mass spectrometer is quickly determined. The amount of ammonia gas is released, and materials with good reversibility of hydrogen absorption and release are screened out.

Benefits of technology

This method can analyze the ammonia release amount of metal amino acid samples within 1 hour to 3 hours, reduce the material detection time, provide rich data information, initially judge the reversibility of the material's hydrogen absorption and release, and assist in the study of its thermal decomposition process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119001050B_ABST
    Figure CN119001050B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for testing the performance of a metal amide hydrogen storage material, which belongs to the field of chemical analysis. The steps include: taking a sample for thermogravimetric analysis, collecting associated gas from a thermogravimetric analyzer at a weightlessness temperature point; transporting the associated gas collected at multiple weightlessness temperature points to a gas chromatography-mass spectrometer respectively, analyzing according to a preset gas chromatography-mass spectrometry analysis program, and generating multiple sample thermal decomposition gas spectra; selecting a sample thermal decomposition gas spectrum generated by ammonia, extracting an ion chromatogram with a mass-to-charge ratio of 17 from it, calculating the first peak area of ​​the ammonia mass spectrum signal, and calculating the ammonia release. It only takes 1 to 3 hours to analyze the ammonia release of the metal amide sample at different temperatures, and the reversibility of hydrogen absorption and desorption of the metal amide hydrogen storage material can be judged from another perspective. Only 20 mg to 100 mg of sample is needed for one test to obtain rich data information.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for testing the performance of a metal amino hydrogen storage material, and belongs to the field of chemical analysis. Background Art

[0002] With the development of industry and the improvement of people's living standards, the demand for energy is also increasing. Hydrogen, as a green energy source with abundant reserves, widespread sources, and high energy density, is attracting widespread attention. The entire hydrogen economy process includes hydrogen production, storage and transportation, fuel cell application, safety, and the development of performance indicators. Hydrogen is produced from green energy sources such as wind and solar power, and then used as fuel in fuel cells or hydrogen internal combustion engines to release energy. The entire process is clean, low-carbon, and does not generate additional pollutants. While relatively mature technologies are currently available for hydrogen production and utilization, hydrogen storage is the bottleneck that restricts the entire hydrogen energy cycle.

[0003] Hydrogen exists in three forms: gaseous, liquid, and solid hydride. Based on this characteristic, three types of hydrogen storage technologies have been developed: high-pressure gaseous hydrogen storage, low-temperature liquid hydrogen storage, and solid-state hydrogen storage using hydrogen-containing materials. Solid-state hydrogen storage, due to its high density and low cost, is considered the most promising hydrogen storage method. Currently, among the many solid-state hydrogen storage materials, metal-amide composite systems are attracting considerable attention due to their high hydrogen storage capacity and suitable thermodynamic properties for hydrogen absorption and desorption.

[0004] The main parameters for measuring the performance of solid-state hydrogen storage materials include hydrogen storage volume density, mass fraction, reversibility of hydrogen addition and desorption, hydrogen addition and desorption rate, and cycle life. Existing techniques for evaluating the reversibility of hydrogen addition and desorption in hydrogen storage materials refer to GB / T 33291-2016, "Pressure-Composition-Isotherm (PCT) Test Method for Reversible Hydrogen Absorption and Desorption of Hydrides," and perform cyclic testing of PCT curves and hydrogen absorption and desorption kinetic curves. The reversibility of hydrogen addition and desorption is measured by comparing the changes in hydrogen absorption and desorption capacity under different cycles. A single cycle test of metal nitrogen hydride hydrogen storage materials takes approximately four hours. To obtain a sufficient sample volume, hundreds or even thousands of cycles are required, making this evaluation method prohibitively time-consuming. Summary of the Invention

[0005] In order to overcome the deficiencies of the prior art, the present invention provides a method for testing the performance of metal amide hydrogen storage materials, which can test the reversibility of metal amide hydrogen storage materials more quickly from another perspective.

[0006] The technical solution adopted by the present invention to solve its technical problem is:

[0007] A method for testing the performance of a metal amide hydrogen storage material comprises the following steps:

[0008] Take a sample and perform thermogravimetric analysis according to the preset thermogravimetric analysis program, and collect the associated gas from the thermogravimetric analyzer at the weight loss temperature point;

[0009] The associated gases collected at the plurality of weight loss temperature points are respectively transported to a gas chromatography-mass spectrometer, and analyzed according to a preset gas chromatography-mass spectrometry analysis program to generate a sample thermal decomposition gas spectrum for the associated gases corresponding to each weight loss temperature point;

[0010] The thermal decomposition gas spectrum of the sample with ammonia produced is selected, and the ion chromatogram with a mass-to-charge ratio of 17 is extracted from it. The first peak area of ​​the ammonia mass spectrometry signal at the corresponding weightlessness temperature point is calculated, and the amount of ammonia released is calculated.

[0011] The performance testing method for metal amide hydrogen storage materials provided in this application only takes 1 to 3 hours to analyze the ammonia release of metal amide samples at different temperatures, which is conducive to screening materials with good reversibility of hydrogen absorption and desorption based on the ammonia release amount; moreover, only 20 mg to 100 mg of sample is needed for one test to obtain rich data information, which is convenient for further research on the material.

[0012] Furthermore, the step of collecting associated gas from the thermogravimetric analyzer includes:

[0013] The associated gas in the thermogravimetric analyzer is transported to a gas sample storage via a first pipeline, and the associated gas collected at different weight loss temperature points is stored in different partitions;

[0014] The step of respectively transporting the associated gases collected at the plurality of weightlessness temperature points to a gas chromatography-mass spectrometer comprises:

[0015] The associated gas in the plurality of partitions is transported in batches to a gas chromatograph-mass spectrometer via a second pipeline.

[0016] When collecting associated gases at different weightlessness temperature points, only the associated gases at the moment of passing the weightlessness temperature point are collected, then stored in partitions, and finally subjected to gas chromatography-mass spectrometry analysis. This helps to ensure the continuity of the experiment and can accurately distinguish the components produced by the thermal decomposition of the sample at each weightlessness temperature point.

[0017] Furthermore, the first pipeline, the second pipeline and the gas sample storage are all kept at 200° C., which is conducive to the thermal decomposition products to maintain the component ratio as much as possible when they are just thermally decomposed.

[0018] Furthermore, the step of taking a sample and performing thermogravimetric analysis according to a preset thermogravimetric analysis program, and collecting associated gas from the thermogravimetric analyzer at the weightlessness temperature point includes:

[0019] Take two parts of metal amide type hydrogen storage material;

[0020] The first portion of the material is subjected to thermogravimetric analysis according to the preset thermogravimetric analysis program to obtain a TG curve and a DSC curve, with the temperature at which the TG curve begins to lose weight as the starting point and the temperature at which the exothermic process of the DSC curve ends as the end point to obtain the temperature range of weight loss before decomposition of the sample;

[0021] Selecting a plurality of weight loss temperature points within the weight loss temperature range before decomposition;

[0022] The second portion of material is used as the sample, and thermogravimetric analysis is performed according to the preset thermogravimetric analysis program, and associated gas is collected from the thermogravimetric analyzer at multiple weight loss temperature points.

[0023] That is, in a complete experiment, the first sample undergoes only thermogravimetric analysis, while the second sample undergoes thermogravimetric analysis followed by gas chromatography-mass spectrometry. The purpose of the first sample is to provide a preliminary indication of the temperature at which the metal amide to be tested begins to decompose and the temperature range within which thermal weight loss occurs, thus facilitating the determination of the weight loss temperature. Since gas analysis does not require collection for the first sample, the mass of the first sample can be less than that of the second sample.

[0024] Furthermore, in the step of selecting a plurality of weight loss temperature points within the weight loss temperature range before decomposition, the selected points are required to meet the following requirements:

[0025] The extreme low and extreme high values ​​of the weight loss temperature point span more than 60% of the preset temperature range and span the continuous endothermic-exothermic peak of the DSC curve;

[0026] The preset temperature range starts at the temperature at which the sample begins to lose weight and ends at the end temperature of the continuous endothermic-exothermic peak in the DSC curve.

[0027] Furthermore, the step of calculating the ammonia release amount includes:

[0028] Substituting the first peak area into a calibration equation to obtain the ammonia release amount;

[0029] The step of obtaining the correction equation includes:

[0030] Standard substances of different masses are grouped and subjected to thermogravimetric analysis according to the preset thermogravimetric analysis program, and multiple groups of product gases are collected from the thermogravimetric analyzer;

[0031] The product gases of each group are respectively transported to a gas chromatography-mass spectrometer, and analyzed according to a preset gas chromatography-mass spectrometry analysis program to obtain a thermal decomposition gas spectrum of the standard substance, which is compared with a standard spectrum library to obtain the chromatographic peak position of ammonia in the thermal decomposition gas spectrum of the standard substance, and the ion chromatogram with a mass-to-charge ratio of 17 is extracted to obtain the second peak area of ​​the ammonia mass spectrometry signal;

[0032] The calibration equation is obtained by fitting a linear regression equation using the least squares method, with the theoretical ammonia mass generated by the thermal decomposition of the standard as the independent variable and the second peak area as the dependent variable.

[0033] The standard spectrum library can be the NIST spectrum library.

[0034] Furthermore, the step of selecting the thermal decomposition gas spectrum of the sample produced by ammonia includes:

[0035] The thermal decomposition gas spectrum of the sample in which ammonia is produced is selected according to the retention time of the chromatographic peak position of ammonia in the thermal decomposition gas spectrum of the standard substance.

[0036] Furthermore, the method for testing the performance of the metal amide hydrogen storage material further comprises the following steps:

[0037] Comparing the thermal decomposition gas spectrum of the sample with the standard spectrum library to determine the gas composition of the sample decomposed at the weightlessness temperature point is conducive to simply analyzing the reversibility of hydrogen absorption and desorption of the material in one experiment, and incidentally analyzing more parameters in the thermal decomposition process of the material.

[0038] Furthermore, the standard substance is ammonium bicarbonate. Ammonium bicarbonate has a low thermal decomposition temperature and a fast thermal decomposition rate, and the decomposed gas is a mixed gas with simple components. This is conducive to determining the retention time of ammonia produced by thermal decomposition during gas chromatography, and is conducive to developing a calibration equation for quantifying ammonia in the mixed gas produced by the thermal decomposition of metal amides.

[0039] Furthermore, the settings of the preset thermogravimetric analysis program include: continuously introducing helium at a flow rate of 30 mL / min, and heating from room temperature to 350° C. at a heating rate of 8° C. / min.

[0040] Furthermore, the settings of the preset gas chromatography-mass spectrometry analysis program include: the injection port temperature is set to 200°C, the split ratio is 2:1, the gas column oven is first heated from 50°C to 200°C at a rate of 10°C / min, the chromatographic column is a styrene-divinylbenzene copolymer gas chromatography column equipped with an integrated particle trap, the column flow rate is 2 mL / min, the mass spectrometer uses an EI source, the ionization energy is 70 eV, the ion source temperature is 230°C, the MS quadrupole temperature is 150°C, the full scan mode, and the scanning range is 10 m / z-350m / z.

[0041] The beneficial effects of the present invention are as follows: the performance testing method of the metal amide hydrogen storage material of the present invention takes a short time, and the ammonia release amount of the metal amide sample at different temperatures can be analyzed in only 1 to 3 hours. The reversibility of hydrogen absorption and desorption of the metal amide hydrogen storage material can be judged from another perspective. Only 20 mg to 100 mg of sample is needed for one test to obtain rich data information. In addition to being able to preliminarily judge the reversibility of the material, it is also conducive to further research on the material.

[0042] Other features and advantages of the present application will be described in the following description, and in part will become apparent from the description, or understood by practicing the present application. The purpose and other advantages of the present application can be realized and obtained by the structures particularly pointed out in the written description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a connection diagram of the analytical instruments provided in the embodiments of the present application.

[0044] Figure 2 This is the thermogravimetric analysis result of a certain metal amino compound.

[0045] Figure 3 This is the calibration curve prepared using the standard substance in Example 1.

[0046] Figure 4 This is a graph showing the thermogravimetric analysis results of the sample from Example 1.

[0047] Figure 5 This is a graph of the peak area of ​​the ammonia gas mass spectrometry signal corresponding to different weight loss temperature points of the sample in Example 1.

[0048] Figure 6 This is the calibration curve prepared using the standard substance in Example 2.

[0049] Figure 7 This is a graph showing the thermogravimetric analysis results of the sample from Example 2.

[0050] Figure 8 This is a graph of the ammonia mass spectrometry signal peak area corresponding to different weight loss temperature points of the sample in Example 2. Reference numerals: 1, thermogravimetric analyzer; 2, gas chromatograph-mass spectrometer; 3, gas sample storage; 31, first pipeline; 32, second pipeline; 33, storage tank. DETAILED DESCRIPTION

[0051] The principle of solid-state hydrogen storage is the "adsorption" and "desorption" of hydrogen by metal hydrides. When hydrogen comes into contact with these metals under certain pressures and temperatures, it forms chemical bonds with the metals, forming hydrides, and the hydrogen is "solidified" in the metal lattice. By heating or reducing pressure, the hydrogen stored in the material is released and restored to gaseous hydrogen. However, adsorption and desorption are not 100% reversible. When researchers develop a new hydrogen storage material, they need to evaluate its various properties, and the evaluation of the reversibility of hydrogen adsorption and desorption is particularly important.

[0052] As a type of solid-state hydrogen storage material, metal amide composite system hydrogen storage materials release ammonia as a byproduct during the dehydrogenation process. Most of the ammonia produced comes from the self-decomposition of the metal amide, and the higher the temperature, the greater the amount of ammonia released. After 270 cycles of hydrogen absorption and desorption, the hydrogen absorption and desorption capacity will decline by 25%, of which about 1 / 3 is due to the release of ammonia. [1] , thereby reducing the reversibility of hydrogen addition and desorption of the material; this scheme reversely infers based on this conclusion, and measuring the amount of ammonia released can quickly judge the reversibility of hydrogen addition and desorption of metal amino hydrogen storage materials from another perspective.

[0053] It should be noted that the test results of this application are not completely equivalent to traditional hydrogen absorption and desorption cycle tests, but they can indeed preliminarily determine the reversibility of hydrogen absorption and desorption of metal amino hydrogen storage materials. It can be used as a preliminary screening method to reduce the time required to test various parameters in the process of developing new materials. It can not only make a preliminary judgment on the reversibility of hydrogen absorption and desorption of the material, but also generate a lot of data information related to the thermal decomposition of the material, which is helpful for the evaluation of other items of the material.

[0054] The ammonia intermediate reaction mechanism suggests that ammonia is released as an intermediate during the thermal decomposition of metal amides, which then rapidly reacts with metal hydrides to produce hydrogen. Measuring the amount of ammonia released can help demonstrate the reaction mechanism of metal amides.

[0055] In addition, hydrogen fuel cells are key components that affect the performance of motor vehicles. Solid-state hydrogen storage materials provide hydrogen for fuel cells, and hydrogen is electrochemically oxidized to generate electricity. The trace amount of ammonia contained in hydrogen can affect the performance of the battery and even poison it. It is generally understood that ammonia reacts with hydrogen ions (H) in the electrolyte membrane. + ) reacts to form ammonium ions (NH4 + ) leads to a decrease in the conductivity of the electrolyte membrane, which can irreversibly affect battery performance. Due to the significant toxicity of ammonia, the International Fuel Cell Standardization Organization has set a standard concentration of ammonia in hydrogen at 0.1 parts per million (ppm). Reducing ammonia release is crucial in the research of metal-amide composite hydrogen storage materials.

[0056] This application can not only make a preliminary judgment on the reversibility of hydrogen absorption and desorption of the material, but also help to study the reaction mechanism of metal amides and monitor the adverse effects of metal amides on fuel cells.

[0057] If we refer to GB / T 33291-2016 "Pressure-Composition-Isotherm (PCT) Test Method for Reversible Hydrogen Absorption and Desorption of Hydride" and conduct cyclic testing of PCT curves and hydrogen absorption and desorption kinetic curves, we can only compare the hydrogen absorption and desorption capacities, but cannot directly determine the type of gas produced and the amount of ammonia released, which is not convenient for subsequent research on the reaction mechanism of metal amino hydrogen storage materials.

[0058] According to GB / T 43361-2023, "Gas Analysis - Validation of Hydrogen Fuel Analysis Methods for Proton Exchange Membrane Fuel Cells for Road Vehicles," commonly used methods for testing ammonia in hydrogen are Fourier transform infrared spectroscopy and continuous wave cavity ring-down spectroscopy, while other impurity gases are detected by gas chromatography. Gas chromatography requires collecting more than 0.1 L of hydrogen released from the hydrogen storage material, while Fourier transform infrared spectroscopy and continuous wave cavity ring-down spectroscopy require collecting more than 0.5 L of gas. During gas sampling, the entire system is purged with the test gas to avoid air interference, so more gas samples are required. To investigate the purity of hydrogen produced by a material under different conditions, repeated gas sampling is required. Consequently, a single gas production test consumes significant material and labor costs. To save costs, typical material research typically synthesizes small samples for exploratory purposes, making it difficult to evaluate the purity of hydrogen storage material gas using these methods.

[0059] In response to the above problems, the performance testing method of the metal amide hydrogen storage material of the present application is implemented according to the following steps:

[0060] S1: Take a sample and perform thermogravimetric analysis according to the preset thermogravimetric analysis program, and collect the associated gas from the thermogravimetric analyzer at the weight loss temperature point.

[0061] S2: The associated gases collected at multiple weight loss temperature points are respectively transported to a gas chromatography-mass spectrometer, and analyzed according to a preset gas chromatography-mass spectrometry analysis program to generate a sample thermal decomposition gas spectrum for the associated gases corresponding to each weight loss temperature point.

[0062] S3: Select the thermal decomposition gas spectrum of the sample with ammonia produced, extract the ion chromatogram with a mass-to-charge ratio of 17 from it, calculate the first peak area of ​​the ammonia mass spectrometry signal at the corresponding weightlessness temperature point, and calculate the amount of ammonia released.

[0063] This method can be achieved by Figure 1 The structure shown is realized. The thermogravimetric analyzer 1 is connected to the inlet of the gas sample storage 3 through the first pipeline 31, and the outlet of the gas sample storage 3 is connected to the gas chromatography-mass spectrometry instrument 2 ( Figure 1 (GC stands for gas chromatography, and MS stands for mass spectrometry). The first pipeline 31 and the second pipeline 32 can be heated pipelines, each temperature adjustable and wrapped with insulation material. The temperature of the gas sample reservoir 3 and the heated pipelines is adjusted to 200°C and maintained constant.

[0064] Accordingly, the step of collecting associated gas from the thermogravimetric analyzer in step S1 includes:

[0065] The associated gas in the thermogravimetric analyzer is transported to the gas sample storage via the first pipeline, and the associated gas collected at different weight loss temperature points is stored in different partitions.

[0066] The step of respectively conveying the associated gases collected at multiple weightlessness temperature points to the gas chromatography-mass spectrometry in step S2 includes conveying the associated gases in multiple partitions to the gas chromatography-mass spectrometry in batches via the second pipeline.

[0067] The aforementioned partitions can be multiple independent storage tanks 33 within the gas sample reservoir 3. Thermogravimetric analyzer and gas chromatograph-mass spectrometer analysis techniques require a sample volume of 20 mg to 100 mg per test. The gas produced by the thermogravimetric analyzer is stored in the gas sample reservoir, with each tank collecting and storing 250 μL of gas. This allows for rich data with a small sample volume, resulting in greater cost savings compared to conventional hydrogen purity analysis.

[0068] Specifically, the preset thermogravimetric analysis program settings include: continuously introducing helium at a flow rate of 30 mL / min, and heating from room temperature to 350° C. at a heating rate of 8° C. / min. Subsequent Examples 1 and 2 were both subjected to thermogravimetric analysis according to this program.

[0069] The preset gas chromatography-mass spectrometry analysis program settings included: selecting a highly inert inlet, setting the inlet temperature to 200°C, a split ratio of 2:1, heating the gas column oven from 50°C to 200°C at a rate of 10°C / min, selecting a styrene-divinylbenzene copolymer gas chromatography column (30 m x 0.32 mm x 20 μm) with an integrated particle trap, a column flow rate of 2 mL / min, and employing an EI high-sensitivity inert ion source with an ionization energy of 70 eV, an ion source temperature of 230°C, an MS quadrupole temperature of 150°C, and full scan mode over a scan range of 10 m / z to 350 m / z. Subsequent Examples 1 and 2 were analyzed by gas chromatography-mass spectrometry according to this program.

[0070] The weight loss temperature point is a temperature set by the tester at which the sample will thermally decompose. For example, if a sample decomposes above 120°C, the weight loss temperature point can be set at 125°C, 150°C, etc. Accordingly, during the period when the sample is heated from room temperature to 130°C, the associated gas collected in step S1 is limited to the moment when the associated gas reaches 125°C. During the period when the temperature continues to rise to 160°C, the associated gas is collected only at the moment when it reaches 150°C.

[0071] When faced with a newly synthesized metal amide, it may be impossible to predict its decomposition temperature, but preliminary experiments can be performed to understand its thermal decomposition characteristics.

[0072] For example, take two parts of metal amide type hydrogen storage material;

[0073] The first sample was subjected to thermogravimetric analysis according to a preset thermogravimetric analysis program to obtain a TG curve and a DSC curve. The temperature at which the TG curve begins to lose weight was taken as the starting point, and the temperature at which the exothermic process of the DSC curve ends was taken as the end point to obtain the temperature range of the sample before decomposition;

[0074] Select multiple weight loss temperature points within the weight loss temperature range before decomposition;

[0075] The second material was subjected to thermogravimetric analysis according to a preset thermogravimetric analysis program, and associated gas was collected from the thermogravimetric analyzer at multiple weight loss temperature points.

[0076] The selection of the weight loss temperature point should try to cover the entire range of the metal amide's continuous weight loss as the temperature increases. Therefore, it is preferred that the selection point meet the following requirements:

[0077] The extreme low and extreme high values ​​of the weight loss temperature point span more than 60% of the preset temperature range and span the continuous endothermic-exothermic peaks of the DSC curve;

[0078] The preset temperature range starts at the temperature where the sample begins to lose weight and ends at the temperature where the continuous endothermic-exothermic peaks in the DSC curve end. The following example illustrates this point selection requirement.

[0079] The inventors synthesized a metal amino compound in the project and conducted a thermogravimetric analysis test on it. The results are as follows: Figure 2 shown. Figure 2 In the figure, the upper one is the TG (thermogravimetric) curve, and the lower one is the DSC curve. The horizontal axes of the TG and DSC curves are both heating time and aligned, but the vertical axes are different. The vertical axis of the TG curve is the residual weight of the sample (unit: mg), and the vertical axis of the DSC curve is the heat flow rate (unit: mW). In this test, the starting room temperature is 30°C. The time on the horizontal axis multiplied by the heating rate of 8°C / min in the preset thermogravimetric analysis program plus the starting room temperature is the corresponding heating temperature. Figure 2 The TG curve shows that the sample begins to lose weight at 79°C. Metal amide hydrogen storage materials exhibit a distinct characteristic during thermogravimetric analysis: a sharp endothermic peak on the DSC curve, followed by an exothermic peak. For example, this sample exhibits two peaks between 23.5 and 31 minutes. The end of this exothermic peak serves as the maximum settable weight loss temperature.

[0080] According to the definition of the preset temperature range, the starting point of the preset temperature range is 79°C and the end point is 278°C. According to the selection point requirements, the selection point of the weight loss temperature point can fall within the range of 79°C~278°C, 120°C~278°C, 158°C~278°C, etc. Although 79°C~200°C spans more than 60% of the preset temperature range, it does not cross the continuous endothermic-exothermic peak of the DSC curve and does not meet the selection point requirements. Next, taking the selection point range of 120°C~278°C as an example, 10 weight loss temperature points can be selected, such as 120°C, 130°C, 140°C, 150°C, 180°C, 200°C, 220°C, 240°C, 260°C, and 278°C. Note that the weight loss temperature points may not be equally spaced. Preferably, more dense weight loss temperature points can be set at the continuous endothermic-exothermic peak of the DSC curve.

[0081] In step S3, the step of calculating the amount of ammonia released includes:

[0082] Substitute the first peak area into the calibration equation to obtain the ammonia release amount.

[0083] The steps of obtaining the correction equation include:

[0084] S01: Standard substances of different masses are grouped and subjected to thermogravimetric analysis according to a preset thermogravimetric analysis program, and multiple groups of product gases are collected from the thermogravimetric analyzer.

[0085] S02: Each group of product gases is separately transported to a gas chromatography-mass spectrometer, and analyzed according to a preset gas chromatography-mass spectrometry analysis program to obtain a thermal decomposition gas spectrum of the standard substance. The retention time of the chromatographic peak position of ammonia is obtained by comparing it with the standard spectrum library, and the ion chromatogram with a mass-to-charge ratio of 17 is extracted to obtain the second peak area of ​​the ammonia mass spectrometry signal.

[0086] S03: Using the theoretical mass of ammonia produced by thermal decomposition of the standard as the independent variable and the second peak area as the dependent variable, the least squares method was used to fit the linear regression equation to obtain the calibration equation.

[0087] For example, a gradient of mass amounts of ammonium bicarbonate (20 mg, 40 mg, 60 mg, and 80 mg, high-purity or higher) was placed in the sample chamber of a thermogravimetric analyzer. The thermogravimetric analysis program described above was run to generate chromatograms and mass spectra of the ammonium bicarbonate thermal decomposition gas. The chromatographic peak position (RT) of ammonia was determined by comparison with the NIST spectral library. The ion chromatogram at m / z 17 was extracted to determine the mass spectrometric peak area of ​​ammonia. A linear regression equation was fitted using the least-squares method, with ammonia mass (4.3081 mg, 8.6162 mg, 12.9244 mg, and 17.2325 mg, representing the theoretical ammonia yields from the thermal decomposition of 20 mg, 40 mg, 60 mg, and 80 mg of ammonium bicarbonate, respectively) as the horizontal axis and the mass spectrometric peak area as the vertical axis.

[0088] In step S3, the step of selecting the thermal decomposition gas spectrum of the sample in which ammonia is generated comprises:

[0089] The retention time of the ammonia peak in the thermal decomposition gas spectrum of the standard was compared to select the thermal decomposition gas spectrum of the sample producing ammonia.

[0090] The complete step S3 may be, for example: (1) using the NIST spectral library to search and qualitatively analyze the composition information of the cracking gas; (2) comparing the retention time of the ammonia peak in the chromatogram of the sample and the ammonium bicarbonate thermal decomposition gas to determine whether ammonia is produced; (3) extracting the ion chromatogram of the gas sample with m / z 17 to obtain the mass spectrum signal peak area of ​​ammonia, and substituting it into the calibration equation to obtain the amount of ammonia released.

[0091] Example 1

[0092] Ammonia calibration: Gradient amounts of ammonium bicarbonate (26.76 mg, 45.86 mg, 60.65 mg, and 79.18 mg) were placed in the sample chamber of a thermogravimetric analyzer. After thermogravimetric analysis and gas chromatography-mass spectrometry analysis, the thermal decomposition gas spectrum of the standard material was obtained. This was compared with the NIST chromatographic library to determine the chromatographic peak position of ammonia in the thermal decomposition gas spectrum of the standard material and the retention time of the ammonia peak (approximately starting at 3.2 minutes and ending at approximately 3.7 minutes). The ion chromatogram with a mass-to-charge ratio of 17 at this chromatographic peak (the chromatographic peak position of ammonia in the thermal decomposition gas spectrum of the standard material) was extracted to obtain the ammonia mass spectrometry signal peak area (the second peak area, generated by the gas chromatography-mass spectrometry analysis program). Based on the second peak area and the theoretical ammonia yield, the calibration equation y = 1371119.19x - 7760215.02 was fitted. The fitting curve is shown below. Figure 3 shown.

[0093] Testing of hydrogen storage material sample (doped metal amide): Weigh 48.30 mg of sample into the sample container of thermogravimetric analyzer, run the above thermogravimetric analyzer program, and obtain the thermogravimetric curve of the material, as shown in Figure 2. Figure 4 To observe the data more intuitively, Figure 2 different, Figure 4 The horizontal axes of the TG curve and the DSC curve are still aligned, but the meaning of the horizontal axis is changed to heating temperature; the vertical axis of the TG curve is changed to the percentage of the remaining weight of the sample relative to the initial weight; the vertical axis unit of the DSC curve is changed to watts / gram.

[0094] The gases released by the thermogravimetric analyzer were collected at 60, 100, 110, 120, 160, 180, 185, 190, 200, 210, 220, 230, and 240°C, and then injected into a gas chromatography-mass spectrometer for analysis. 13 gas sample chromatograms and mass spectra were obtained, all of which had chromatographic peaks at 3.2 min to 3.7 min. It was determined that ammonia was generated at all 13 weightlessness temperatures. The part with a mass-to-charge ratio of 17 was extracted to obtain the mass spectrometry signal peak area (response value) of ammonia. The 13 peak areas were plotted on the same graph, as shown in Figure 2. Figure 5 As shown, Figure 5 The horizontal axis is temperature.

[0095] Finally, the ammonia gas mass spectrometry signal peak area was substituted into the calibration curve to obtain the ammonia yield. For example, at 230°C, the ammonia gas peak area of ​​the gas sample was 147,659.18. Substituting this into the fitting equation yielded a total ammonia release of 5.77 mg.

[0096] Example 2

[0097] Ammonia calibration: Gradient amounts of ammonium bicarbonate (21.33 mg, 40.16 mg, 58.77 mg, and 79.58 mg) were placed in the sample chamber of a thermogravimetric analyzer. After thermogravimetric analysis and gas chromatography-mass spectrometry analysis, the thermal decomposition gas spectrum of the standard material was obtained. This was compared with the NIST chromatogram library to obtain the chromatographic peak position of ammonia in the thermal decomposition gas spectrum of the standard material and the retention time of the chromatographic peak position. The ion chromatogram with a mass-to-charge ratio of 17 in this chromatographic peak position was extracted to obtain the ammonia mass spectrometry signal peak area. Based on the second peak area and the theoretical ammonia yield, the calibration equation y = 1320692.901x - 5185040.32 was fitted. The fitting curve is shown as follows: Figure 6 shown.

[0098] Another hydrogen storage material sample (doped metal amide) was tested: 36.17 mg of the sample was weighed into the sample container of the thermogravimetric analyzer. The thermogravimetric analyzer program was run to obtain the thermogravimetric curve of the material, as shown in FIG. Figure 7 shown.

[0099] The gas released by the thermogravimetric analyzer was collected at 100°C, 110°C, 120°C, 160°C, 180°C, 200°C, 220°C, 230°C, and 240°C into a gas sample storage device, and then injected into a gas chromatography-mass spectrometer for analysis. Nine gas sample chromatograms and mass spectra were obtained, confirming that all ammonia was generated. The part with a mass-to-charge ratio of 17 was extracted to obtain the mass spectrometry signal peak area of ​​ammonia. The nine peak areas were plotted on the same graph, as shown in Figure 2. Figure 8 As shown, Figure 8 The horizontal axis is temperature.

[0100] Finally, the ammonia gas mass spectrometry signal peak area is substituted into the calibration curve to obtain the ammonia yield. Taking 180°C as an example, the ammonia gas peak area of ​​the gas sample is 169652.95, which is substituted into the equation to obtain the total ammonia released amount of 4.05 mg.

[0101] This application uses the amount of ammonia released to evaluate the reversibility of hydrogen addition and desorption of metal amide hydrogen storage materials, which is different from the evaluation dimension of the conventional method of comparing the hydrogen absorption and desorption capacity under different cycles after multiple cycles of hydrogen absorption and desorption. The principle of this application being able to quickly and preliminarily determine the reversibility of hydrogen addition and desorption of metal amide hydrogen storage materials is that metal amide hydrogen storage materials release hydrogen when heated, and ammonia is an intermediate gas in the reaction process during normal operation and will not escape easily. The chemical formula of the ammonia intermediate mechanism is as follows:

[0102]

[0103] Ammonia is an intermediate product and will not escape. Normally, it should be immediately converted into other nitrogen-hydrogen compounds and retained within the material. Detection of ammonia escape indicates material wear and tear at that temperature, directly reducing the amount of material participating in hydrogen storage the next time. This can be used to determine the reversibility of hydrogen absorption and desorption. Thermogravimetric analysis and gas chromatography-mass spectrometry (GC-MS) analysis of metal amide samples takes approximately one to three hours. Upon completion, the amount of ammonia released by the material at different temperatures is obtained. This can be used to screen materials with superior reversibility in hydrogen addition and desorption. Comparative cyclic testing of hydrogen absorption and desorption kinetic curves is even more time-efficient.

[0104] The combination of the thermogravimetric analyzer, gas chromatography-mass spectrometry and gas sample storage in this application, as well as various preset condition parameters, is specifically designed to test the release of ammonia from metal amide hydrogen storage materials. It can not only quickly and preliminarily determine the reversibility of hydrogen addition and desorption from metal amide hydrogen storage materials, but can also simultaneously obtain multiple sets of data such as thermal stability information of the material to be tested, precipitation time and precipitation intensity of pyrolysis components, component information of pyrolysis components, pyrolysis gas content, etc., providing richer information on the complex thermochemical reactions of the material, facilitating subsequent research on the change mechanism of the material.

[0105] Throughout this specification, references to terms such as "one embodiment," "certain embodiments," "illustrative embodiments," "examples," "specific examples," or "some examples" indicate that a specific feature, structure, material, or characteristic described in conjunction with the embodiment or example is included in at least one embodiment or example of the present invention. In this specification, illustrative uses of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in any one or more embodiments or examples.

[0106] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.

[0107] References

[0108] [1]WF Luo, J. Wang, K. Stewart, M. Clift and K. Gross. Li-Mg-NH:Recent investigations and development. Journal of Alloys and Compounds,2007,446:336-341.

Claims

1. A method for testing the performance of metal amide hydrogen storage materials, characterized in that: The following steps are involved: Take a sample and perform thermogravimetric analysis according to a preset thermogravimetric analysis program, and collect associated gas from the thermogravimetric analyzer at the weight loss temperature point; The associated gases collected at the plurality of weight loss temperature points are respectively transported to a gas chromatography-mass spectrometer, and analyzed according to a preset gas chromatography-mass spectrometry analysis program, and a sample thermal decomposition gas spectrum is generated for the associated gases corresponding to each weight loss temperature point; Select the thermal decomposition gas spectrum of the sample with ammonia generated, extract the ion chromatogram with a mass-to-charge ratio of 17 from it, calculate the first peak area of ​​the ammonia mass spectrum signal at the corresponding weight loss temperature point, and calculate the ammonia release amount; The step of taking samples for thermogravimetric analysis according to a preset thermogravimetric analysis program and collecting associated gas from the thermogravimetric analyzer at the weight loss temperature point comprises: Take two portions of metal amide type hydrogen storage material; The first material is subjected to thermogravimetric analysis according to the preset thermogravimetric analysis program to obtain a TG curve and a DSC curve, and the temperature at which the TG curve begins to lose weight is taken as the starting point, and the temperature at which the exothermic process of the DSC curve ends is taken as the end point, to obtain the temperature range of weight loss before decomposition of the sample; Selecting a plurality of weight loss temperature points within the weight loss temperature range before decomposition; The second material is used as the sample, and a thermogravimetric analysis is performed according to the preset thermogravimetric analysis program, and associated gas is collected from the thermogravimetric analyzer at a plurality of weight loss temperature points; In the step of selecting a plurality of weight loss temperature points within the weight loss temperature range before decomposition, the selection requirements satisfy: The extreme low value and the extreme high value of the weight loss temperature point span more than 60% of the preset temperature range and span the continuous endothermic-exothermic peak of the DSC curve; The preset temperature range starts at the temperature at which the sample starts to lose weight and ends at the end temperature of the continuous endothermic-exothermic peak in the DSC curve.

2. The method for testing the performance of metal amide hydrogen storage materials according to claim 1, characterized in that: The step of collecting associated gas from the thermogravimetric analyzer comprises: The associated gas in the thermogravimetric analyzer is transported to a gas sample storage device via a first pipeline, and the associated gas collected at different weight loss temperature points is stored in different partitions; The step of respectively transporting the associated gases collected at the plurality of weightlessness temperature points to a gas chromatography-mass spectrometer comprises: The associated gas in the plurality of partitions is transported in batches to a gas chromatograph-mass spectrometer via a second pipeline.

3. The method for testing the performance of metal amide hydrogen storage materials according to claim 2, characterized in that: The first pipeline, the second pipeline and the gas sample storage are all kept at 200°C.

4. The method for testing the performance of metal amide hydrogen storage materials according to claim 1, characterized in that: The step of calculating the ammonia release amount comprises: Substituting the first peak area into a calibration equation to obtain the ammonia release amount; The step of obtaining the correction equation comprises: Taking standard substances of different masses into groups and performing thermogravimetric analysis according to the preset thermogravimetric analysis program, collecting multiple groups of product gases from the thermogravimetric analyzer; The product gases of each group are respectively transported to a gas chromatography-mass spectrometer, and analyzed according to a preset gas chromatography-mass spectrometry analysis program to obtain a thermal decomposition gas spectrum of a standard substance, and compared with a standard spectrum library to obtain a chromatographic peak position of ammonia in the thermal decomposition gas spectrum of the standard substance, and an ion chromatogram with a mass-to-charge ratio of 17 is extracted to obtain a second peak area of ​​ammonia mass spectrum signal; The theoretical ammonia mass generated by the thermal decomposition of the standard substance is used as the independent variable, the second peak area is used as the dependent variable, and the least square method is used to perform linear regression equation fitting to obtain the correction equation.

5. The method for testing the performance of metal amide hydrogen storage materials according to claim 4, characterized in that: The step of selecting the sample thermal decomposition gas spectrum containing ammonia gas comprises: According to the retention time of the chromatographic peak position of ammonia in the thermal decomposition gas spectrum of the standard substance, the thermal decomposition gas spectrum of the sample in which ammonia is produced is selected.

6. The method for testing the performance of metal amide hydrogen storage materials according to claim 4, characterized in that: The steps also include: The thermal decomposition gas spectrum of the sample is compared with the standard spectrum library to determine the gas components decomposed by the sample at the weightlessness temperature point.

7. The method for testing the performance of metal amide hydrogen storage materials according to claim 4, characterized in that: The standard was ammonium bicarbonate.

8. The method for testing the performance of metal amide hydrogen storage materials according to claim 1, characterized in that: The preset thermogravimetric analysis program settings include: continuously introducing helium at a flow rate of 30 mL / min, and heating from room temperature to 350° C. at a heating rate of 8° C. / min; The settings of the preset gas chromatography-mass spectrometry analysis program include: the injection port temperature is set to 200°C, the split ratio is 2:1, the gas column oven is first heated from 50°C to 200°C at a rate of 10°C / min, the chromatographic column uses a styrene-divinylbenzene copolymer gas chromatography column with an integrated particle trap, the column flow rate is 2mL / min, the mass spectrometer uses an EI source, the ionization energy is 70eV, the ion source temperature is 230°C, the MS quadrupole temperature is 150°C, the full scan mode, and the scan range is 10 m / z -350m / z.

Citation Information

Patent Citations

  • Method for measuring element contents by using thermogravimetric-mass spectrometry

    CN109696375A